Analisis Kinerja Keuangan PT Dian Swastatika Sentosa Tbk Periode 2020–2024 - Ni Nengah Nila Cahya Putri; Nengah Sukendri (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study aims to evaluate the financial performance of PT Dian Swastatika Sentosa Tbk during the 2020-2024 period through financial ratio analysis covering liquidity, solvency, profitability, and activity aspects. The method used is a descriptive quantitative approach with time series analysis techniques based on annual financial report data sourced from the Indonesia Stock Exchange. The analysis results show that although the company recorded a loss in 2020 due to the pandemic, PT Dian Swastatika Sentosa Tbk managed a rapid recovery and reached its peak performance in 2022 through acquisition and expansion strategies. Liquidity ratios showed significant strengthening in 2024, with the quick ratio reaching 219%. The company's capital structure also improved, with the debt-to-asset ratio remaining stable in the 43%-52% range since 2021. Profitability indicators (ROA, ROE, ROI, and NPM) show a stable positive trend, reflecting management's efficiency in managing assets and capital to generate profit. Overall, the company has transformed into an entity with solid financial fundamentals and sustainable growth prospects.